‘참동진/영호진미’ 재조합집단을 이용한 품질 관련 양적형질 유전자좌 분석 - 박현수(Hyun-Su Park); 서정환(Jeonghwan Seo); 이창민(Chang-Min Lee); 박송희(Songhee Park); 이건미(Keon-Mi Lee); 박재령(Jae-Ryoung Park); 정오영(O-Young Jeong) (Korean journal of breeding, 2024)
‘Chamdongjin’ is a rice cultivar with a distinctively large grain size and good palatability, similar to ‘Sindongjin,’ which is a mega-cultivar in Korea. ‘Younghojinmi’ is a rice cultivar known for having the highest taste value among premium quality cultivars. In this study, we conducted quantitative trait loci (QTL) analysis of quality-related traits using recombinant inbred lines (RILs) derived from a cross between ‘Chamdongjin’ and ‘Younghojinmi’ to elucidate their genetic interactions. We analyzed 20 traits, including protein content, amylose content, glossiness of cooked rice, 7 traits related to grain appearance, 6 traits related to pasting properties, and 4 traits related to texture. Quality-related QTL were primarily detected on chromosome 3. In particular, GS3, one of the candidate genes for QTL, significantly influenced quality by affecting 14 different traits, including appearance traits such as head rice and the texture of cooked rice. Furthermore, RILs with the gs3 allele, which exhibited the large grains of ‘Chamdongjin,’ showed a lower protein content and higher amylose content than RILs with the GS3 allele. These lines also had lower head rice percentages and higher percentages of whiteness, opacity, and broken rice, indicating an inferior appearance quality. In terms of pasting properties, RILs with the gs3 allele showed a lower pasting temperature, peak viscosity, and breakdown, but a higher setback than RILs with the GS3 allele. Although the gs3 allele did not affect the glossiness, hardness, or toughness of the cooked rice, it resulted in higher adhesiveness and stickiness. Allelic alteration of the preharvest sprouting gene qLTG3-1 was found to affect seven quality-related traits, including pasting properties. Genes related to heading date (Hd18), culm length (SD1), and tiller number (OsTB1) were also associated with quality-related QTL. Alterations in the alleles of these genes caused variations in quality-related traits. Our identification of the association between quality-related traits and key agronomic genes is expected to support the effective development of rice cultivars with improved quality. KCI Citation Count: 0